2003
DOI: 10.1046/j.1095-8649.2003.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent changes in energy metabolism, intracellular pH and blood oxygen tension in the Atlantic cod

Abstract: The effect of acute increase in temperature on oxygen partial pressure (Po2) was measured in the gill arches of Atlantic cod Gadus morhua between 10 and 19° C by use of oxygen microoptodes. Oxygen saturation of the gill blood under control conditions varied between 90 and 15% reflecting a variable percentage of arterial or venous blood in accordance with the position of each optode in the gill arch. The data obtained suggested that arterial Po2 remained more or less constant and arterial oxygen uptake did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 33 publications
7
65
3
Order By: Relevance
“…The maintenance of arterial P O 2 seen during warming in cod is in line with an excess capacity of the ventilatory system for oxygen uptake, if compared to oxygen distribution via circulation. However, arterial P O 2 fell drastically above 16 • C (Sartoris et al, 2003b), presumably indicating the temperature at which a minimum threshold P v,O 2 is reached in cod with the result of cardiac failure and organismic collapse.…”
Section: Evidence For Temperature Induced Hypoxia In Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…The maintenance of arterial P O 2 seen during warming in cod is in line with an excess capacity of the ventilatory system for oxygen uptake, if compared to oxygen distribution via circulation. However, arterial P O 2 fell drastically above 16 • C (Sartoris et al, 2003b), presumably indicating the temperature at which a minimum threshold P v,O 2 is reached in cod with the result of cardiac failure and organismic collapse.…”
Section: Evidence For Temperature Induced Hypoxia In Fishmentioning
confidence: 99%
“…They found that heart rate in rainbow trout decreased at temperatures above 24 • C, whereas ventilation remained virtually unchanged until death of the animals occurred. In cod implanted with micro-optodes in gill blood vessels, Sartoris et al (2003b) demonstrated that arterial oxygen tensions (P a,O 2 ) remained unaffected by progressive warming. However, venous oxygen tension (P v,O 2 ) dropped progressively during warming, in line with limited cardiac rather than ventilatory performance.…”
Section: Evidence For Temperature Induced Hypoxia In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, exposure to acidified sea water may act to lower the ceiling of organismal tolerance of high temperatures through changes in metabolism [4,17,18], whereas warmer temperatures may alter the permeability of cell membranes [19] and reduce the ability of organisms to regulate intracellular pH [20]. To explore the potential response of larval purple sea urchins to these co-occurring factors, we cultured larvae under conditions that mimicked future ocean change in the CCLME and assessed organismal performance across multiple levels of biological organization.…”
Section: Introductionmentioning
confidence: 99%
“…Peak position and signal integrals were analyzed using a specially adapted automatic fit routine as described in (21,22). Metabolite concentrations from peak integrals were calculated as described in (23). 4.…”
Section: Nmr Hardwarementioning
confidence: 99%